Implementasi Think Pair Share untuk Meningkatkan Problem Solving Siswa Kelas 5 SD - Yulvia Mardlatillah; Devi Laili Maesaroh; Erika Oktaviana Putri (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study aims to analyze the implementation of the Think Pair Share (TPS) learning model in improving problem solving skills in fractional materials for grade V students at SD Negeri 3 Mantingan. The background of this research is the low ability of students to solve fractional problems, mainly due to procedural misconceptions and lack of opportunities to discuss and construct understanding collaboratively. The method used is the Kemmis and McTaggart model Class Action Research (PTK), which consists of four stages: planning, action, observation, and reflection. The research was conducted in one cycle, involving 28 students as subjects. Data collection was carried out through evaluation tests (pre-cycle and cycle I) as well as observation of student learning activities. The results of the study showed a significant increase in problem solving ability. The average score of students increased from 36.43 in the pre-cycle to 93.21 in the first cycle, with a t-test of 25.18 and a p< value of 0.001, indicating a high significance. Learning completeness increased from 0% to 100%. The TPS model has been proven to be able to overcome misconceptions, especially through the peer scaffolding process in the "pair" stage, which helps students in identifying variables and choosing the right calculation operations. In addition, there was an increase in students' collaborative skills in terms of expressing opinions and asking questions, with an achievement range between 68% to 75%. The main obstacles faced in the implementation of polling stations are the management of discussion time and class noise. However, this was successfully overcome through the use of timers and Student Worksheets (LKPD) equipped with scaffolding questions. It can be concluded that the TPS model is an innovative and effective approach in improving mathematical problem solving skills contextually, in line with the principles of the Independent Curriculum.